Magnetic isotope of magnesium 25Mg accelerates the reaction of ATP hydrolysis catalyzed by myosin - Koltover, V.K.; Labyntseva, R.D.; Lul’ko, A.A.; Karandashev, V.K.; Kosterin, S.A. (Reports of the National Academy of Sciences of Ukraine, 2014)
Among three stable magnesium isotopes 24Mg, 25Mg, and 26Mg with natural abundance 79, 10, and 11%, only 25Mg has the nuclear spin (I = 5/2) and, therefore, the nuclear magnetic moment. Two other isotopes, 24Mg and 26Mg, are spinless (I = 0) and, hence, have no magnetic moment. In this work, we have revealed that magnetic isotope 25Mg, by comparison to nonmagnetic isotopes 24Mg and 26Mg, essentially stimulates, by 2–2.5 times, the enzyme ATP hydrolysis reaction catalyzed by myosin isolated from smooth muscles of uterus. The catalytic effect of the nuclear spin of 25Mg has been observed at the usual physiological concentrations of MgCl2, at 5 mM. Thus, we have, for the first time, documented the magnetic isotope effect in the enzyme hydrolysis of ATP by myosin.